Molecular Mechanisms of Synaptic Plasticity: Dynamic Changes in Neurons Functions - Martella, Giuseppina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The human brain has hundreds of billions of neurons, and at least 7 million dendrites have been hypothesized to exist for each neuron, with over 100 trillion neuron-neuron, neuron-muscle, and neuron-endocrine cell synapses [1,2]. Our body continually receives stimuli from the outer environment, and our brain's ability to respond to these stimuli is ensured through synaptic processes, motivating the foundations of this Special Issue.This reprint aims to underline the role of synaptic plasticity phenomena in our body and clarify the mechanism operated by neurons to guarantee these phenomena. The collection in the Issue comprises 14 papers, including 8 reviews and 6 original works, one of which is a protocol for differentiating neurons from human stem cells, and 5 are preclinical works.